Differentiated services dynamic spectrum access strategy for cognitive wireless mesh network - Rui-fang LI; Quan LIU; Ren-fa LI (Tongxin xuebao)
Dynamic spectrum access (DSA) is an important design aspect for cognitive radio network.Common access of multi-type services having different quality of service (QoS) requirements is the important characteristic of cognitive wireless mesh network.Differentiated service (DS) is the key to realize the high efficiency use of spectrum resources and to guarantee the high quality transmission of services.In order to satisfy the demand for multi-type services,a differentiated services dynamic spectrum access strategy was proposed.In this strategy,the unlicensed user traffic was divided into three priority classes.The DSA scheme uses different access mechanisms for the three classes of unlicensed users.The real-time traffic selectes available channel set according to the shortest expected delay to reduce the transmission time and the probability of appearance of licensed user during data transmission process.The general traffic selectes the channel of largest successful transmission probability to avoid spectrum handoff.The theoretical and experimental results show that,when compared with the traditional cognitive networks DSA strategy,the proposed strategy is able to guarantee different QoS for the various services,shorter transmission delay for higher priority services,reducing the probability of transmission interruption and better throughput performance when the vacancy rate of licensed channel is major and heavy network load.